PREDICTING EMPLOYEE PERFORMANCE FROM THE PERSPECTIVE OF COMMUNICATION: THE MODERATING ROLE OF EMPLOYEE MOTIVATION - Shu, Efin; Chenova, Clarence (Center for Economic Studies Universitas Katolik Parahyangan, 2024)
The development of the hospitality industry is strongly linked to employee performance. It is essential for every employee to achieve good performance for the hotel's major goals to be met. Employee performance can be influenced by the way they communicate and is related to their motivation. On the TripAdvisor website, there have been complaints from guests regarding employee performance or services. The purpose of this research is to determine the influence of communication on employee performance with the moderation of employee motivation at The Apurva Kempinski Bali. This research uses a quantitative approach. Data collection was carried out by distributing questionnaires with the research population being all employees who work at The Apurva Kempinski Bali. Sample of 70 people was collected using the simple random sampling technique. The data was analyzed using the statistical software PLS SEM 4.0. As a result, both hypotheses are accepted. Communication influences employee performance positively, and employee motivation moderates the relationship between communication and employee performance positively. Both hypotheses result in a significant relationship. Since the relationship between communication and employee performance is quite strong, therefore, the management of Apurva Kempinski Bali is recommended to maintain its communication efforts by emphasizing two-way communication, whether verbally or in writing.